Effects of Motor-level Electrical Stimulations on Postprandial Glucose Levels in Non-Diabetic Young Individuals - Han-Hung Huang; Shelly D Weise; Man-Soo Ko; Trevor Hansen; Annika Johnson; Charity McCluskey (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2017)
Background and objectives: Motor-level electrical stimulation (MES) has been shown to improve glucose tolerance and glucose uptake in both animals and humans.  Recently, MES has been shown to improve the blood glucose control in people with Type 2 Diabetes (T2D).  There are several types of MES applied in physical therapy clinics.  However, it is unknown what types of MES optimally decrease postprandial glucose level.  The purpose of this study was to compare the effects of three different types of MES on postprandial glucose levels in healthy non-diabetic subjects.  Methods: Twenty-eight subjects were randomly assigned to four groups: MES 1, MES 2, MES 3 and the control group.  All subjects participated in an overnight fast of at least 8 hours and had their fasting blood glucose measured.  Subjects were given a glucose supplement to drink within 10 minutes, rested in supine for 30 minutes then the second glucose level was measured.  Subjects received a 30-minute MES treatment (except for the control group) followed by the third blood glucose level test.  Subjects then rested an additional 30 minutes followed by obtaining the final blood glucose measurement.  VO2 levels were monitored every 30 seconds, and heart rate was monitored every 3 minutes throughout the 90 minute study.    Results: There were no significant differences between groups on glucose levels and heart rate throughout the study.  The MES 2, Russian Current, demonstrated a statistically significant increase of 10% in VO2 toward the end of treatment.   Conclusions:  In this preliminary study, MES seems to have no effects on lowering postprandial glucose levels in healthy non-diabetic subjects.  However, Russian Current may have a potential for optimally simulating physical activity.   Future research is required with a more extended sampling method, a larger sample size, more intensive MES experimental protocols and a continuous glucose monitoring technique.